Interindividual and intraindividual differences in recovery of German junior female ice hockey players during 2020 World Championship Division IA tournament - Asja Kiel; Reinhold Kliegl; Annika Hof zum Berge; Karl Schwarzenbrunner; Christian Puta; Lisa Kullik; Sarah Jakowski; Michael Kellmann (Scientific Reports)
Abstract World Championship tournaments pose multiple possible recovery-challenging conditions in ice hockey. This investigation aimed at assessing subjective recovery patterns of the German women’s junior national ice hockey team during preparation camp and tournament of the 2020 World Championship Division IA. Players completed the German paper-pencil version of the Short Recovery and Stress Scale regularly over the 14-day survey period. The assessment analyzed potential recuperative effects of overnight recovery and recovery during the day reflected in recovery-stress states. Specifically, linear mixed modelling (LMM) was used to determine inter- and intraindividual response- and effect-profiles on recovery processes and changes over time. Three sets of contrasts were specified à priori for planned comparisons. Regarding main effects, results showed favorable recovery-stress states in the morning. Recovery generally seemed to decrease throughout the day and a generally higher recovery level during the tournament phase in comparison to the preparatory camp period was indicated. Results emphasized the need for considering interindividual differences concerning the perception of different recovery facets. This study could serve as a starting point for introducing the LMM approach into sports science for the examination and presentation of individual recovery and training response patterns and individual cases with recourse to group statistics.